INFLUENCE OF NUTRIENTS ON WINTER WHEAT YIELD IN THE CONDITIONS OF THE WESTERN FOREST-STEPPE OF UKRAINE - Lykhochvor В.; Kosylovych Г.; Andrushko О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
To optimize the winter wheat fertilization system, field studies were conducted on dark gray podzolic soil in the conditions of the Western Forest-Steppe of Ukraine. The soil of the experimental site is dark gray, podzolic, light loamy with a humus content of 2.5–2.6 %. Weather conditions in the years of research were quite contrasting and differed from the average long-term data both in the amount of precipitation and in terms of temperature. During the year, 760 mm precipitation in 2018, 818 mm in 2019, and 710 mm in 2020, with a long-term average of 615 mm. The amount of precipitation in June 2018 and in May 2019 created conditions of excessive moisture, which led to reduced yields. Air temperature during the years of research was not a limiting factor in yield growth. In 2018, the average monthly temperature was 8.8 °C, in 2019 9.1 °C, in 2020 9.4 °C, with a long-term average of 7.8 °C. The inﬂuence of nitrogen (N180), phosphorus (P60), potassium (К90), sulfur (S30), magnesium (Mg20) foliar application of Intermag grain fertilizers (2 l/ha) were studied. Under the inﬂuence of fertilizers, the structure of the crop changed, in particular, the number of ears increased from 480 pcs/m2 in control to 642 pcs/m2 at the highest rate of fertilizers, grain weight per ear - from 0.78 g to 1.48 g respectively. The grain yield of winter wheat of the Kubus variety increased from 3.64 t/ha on the option without fertilizers to 9.14 t/ha with the application of N180P60K90S30Mg20 + Intermag microfertilizer, i.e. by 5.50 t/ha, or 151.1 %. The largest increase of grain was provided by nitrogen fertilizers – 2.94 t/ha (80.8 %). Phosphorus fertilizers, first of all, provided better development of the root system and increased the number of grains in the ear, as a result, the yield increased to 7.41 t/ha, or by 0.83 t/ha. The increase in yield by 0.64 t/ha under the influence of potash fertilizers was also due to better ear grain. Under application of potassium, phosphorus, sulfur, magnesium and microfertilizers the yield increased by 2.56 t/ha (70.3 %).